2023
DOI: 10.1007/s13555-023-00891-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Clinical Management of Atopic Dermatitis: A Survey of Three Physician Specialties in the Middle East

Abstract: Introduction: Atopic dermatitis (AD) is a complex inflammatory disease of the skin that has a significant impact on the well-being of patients and their families. The prevalence of AD has increased in developing countries and regions, including the Middle East. Despite similarities in the presentation of the disease, there is a lack of consistent management and treatment guidelines for AD. The objective of this survey was to develop further insight into the management patterns of AD from dermatologists, pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…A study by Ammoury et al evaluated the management strategies of physicians in Egypt, Lebanon, UAE, and Saudi Arabia and found that there is a significant variation in types of treatments used, referral patterns, and treatment familiarity [2]. This study highlights the lack of a standardized approach to AD management in many countries in the Middle East.…”
Section: Guidelines and Treatment Availabilitymentioning
confidence: 95%
See 4 more Smart Citations
“…A study by Ammoury et al evaluated the management strategies of physicians in Egypt, Lebanon, UAE, and Saudi Arabia and found that there is a significant variation in types of treatments used, referral patterns, and treatment familiarity [2]. This study highlights the lack of a standardized approach to AD management in many countries in the Middle East.…”
Section: Guidelines and Treatment Availabilitymentioning
confidence: 95%
“…Historically, the prevalence of AD throughout the Arab Middle East has been lower than North America and Europe; however, AD prevalence is increasing in the region due to many factors potentially including increasing urbanization and pollution [2]. Due to the large environmental, socioeconomic, and sociocultural heterogeneity of the Arab Middle East, prevalence varies greatly across and within countries.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations